Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 33823 by 33 last updated on 25/Apr/18

  solve :    I = ∫_0 ^π  (((r−R cosθ) sin θ )/((R^(2 ) + r^2  − 2Rr cos θ)^(3/2) )) dθ  for   r < R  and r > R  respectively.

solve: I=π0(rRcosθ)sinθ(R2+r22Rrcosθ)3/2dθ forr<R andr>Rrespectively.

Answered by MJS last updated on 26/Apr/18

∫u′v=uv−∫uv′  u′=((sin θ)/((r^2 +R^2 −2rRcos θ)^(3/2) )); v=r−Rcos θ  u=−(1/(rR(r^2 +R^2 −2rRcos θ)^(1/2) )); v′=Rsin θ        [((∫((sin θ)/((r^2 +R^2 −2rRcos θ)^(3/2) ))dθ=)),((     [t=r^2 +R^2 −2rRcos θ → dx=(dt/(2rRsin θ))])),((=(1/(2rR))∫(1/t^(3/2) )dt=−(1/(rRt^(1/2) )))) ]  uv=−((r−Rcos θ)/(rR(r^2 +R^2 −2rRcos θ)^(1/2) ))  −∫uv′=∫((sin θ)/(r(r^2 +R^2 −2rRcos θ)^(1/2) ))=       [with the same substitution as above]  =(((r^2 +R^2 −2rRcos θ)^(1/2) )/(r^2 R))  ∫(((r−Rcos θ)sin θ)/((r^2 +R^2 −2rRcos θ)^(3/2) ))=  =−((r−Rcos θ)/(rR(r^2 +R^2 −2rRcos θ)^(1/2) ))+(((r^2 +R^2 −2rRcos θ)^(1/2) )/(r^2 R))+C=  =((R−rcos θ)/(r^2 (√(r^2 +R^2 −2rRcos θ))))+C=F(θ)  F(π)−F(0)=((R+r)/(r^2 ∣R+r∣))−((R−r)/(r^2 ∣R−r∣))  r, R>0  r<R ⇒ F(π)−F(0)=0  r>R ⇒ F(π)−F(0)=(2/r^2 )

uv=uvuv u=sinθ(r2+R22rRcosθ)32;v=rRcosθ u=1rR(r2+R22rRcosθ)12;v=Rsinθ [sinθ(r2+R22rRcosθ)32dθ=[t=r2+R22rRcosθdx=dt2rRsinθ]=12rR1t32dt=1rRt12] uv=rRcosθrR(r2+R22rRcosθ)12 uv=sinθr(r2+R22rRcosθ)12= [withthesamesubstitutionasabove] =(r2+R22rRcosθ)12r2R (rRcosθ)sinθ(r2+R22rRcosθ)32= =rRcosθrR(r2+R22rRcosθ)12+(r2+R22rRcosθ)12r2R+C= =Rrcosθr2r2+R22rRcosθ+C=F(θ) F(π)F(0)=R+rr2R+rRrr2Rr r,R>0 r<RF(π)F(0)=0 r>RF(π)F(0)=2r2

Terms of Service

Privacy Policy

Contact: info@tinkutara.com